2012
DOI: 10.1038/nm.2684
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A produced by αβ T cells drives airway hyper-responsiveness in mice and enhances mouse and human airway smooth muscle contraction

Abstract: Emerging evidence suggests that the TH17 subset of αβ T cells contributes to the development of allergic asthma. In this study we found that mice lacking αvβ8 on dendritic cells failed to generate TH17 cells in the lung and were protected from AHR in response to house dust mite and ovalbumin sensitization and challenge. Because loss of TH17 cells inhibited airway narrowing without obvious effects on airway inflammation or epithelial morphology, we examined the direct effects of TH17 cytokines on mouse and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
336
8
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 417 publications
(374 citation statements)
references
References 55 publications
20
336
8
10
Order By: Relevance
“…IL-13, TNF-α, and IL-17A each enhance calcium sensitivity through a signaling pathway consisting of NF-κB activation, increased RhoA and ROCK2 expression, and ROCK2 phosphorylation of MLCP (2)(3)(4)38). We show here that Mfge8 inhibits ASM contraction in part by suppressing this pathway.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…IL-13, TNF-α, and IL-17A each enhance calcium sensitivity through a signaling pathway consisting of NF-κB activation, increased RhoA and ROCK2 expression, and ROCK2 phosphorylation of MLCP (2)(3)(4)38). We show here that Mfge8 inhibits ASM contraction in part by suppressing this pathway.…”
Section: Discussionmentioning
confidence: 60%
“…Although a significant body of research has focused on understanding the effects of IL-13, IL-17A, and other cytokines on coordinating the immune response in asthma (17,23,(44)(45)(46), the importance of these mediators on ASM contractility has been more recently appreciated (2,4). Most of the therapeutic strategies in asthma target specific steps of the inflammatory response with varying success (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…123 Recently, one study showed that IL-17 but not IL-17F directly drove pulmonary hyper-responsiveness by promoting smooth muscle contractions in the airway. 124 Because IL-17 also induces the production of mucins such as MUC5AC and MUC5B by airway epithelial cells, 125,126 these findings indicate that IL-17 may promote pulmonary allergies by inducing airway remodelling in addition to its inflammatory effects.…”
Section: Il-17dmentioning
confidence: 99%